Flutter for dummies - Burd, Barry (For Dummies, 2020)
"Create awesome iOS and Android apps with a single tool! Flutter is an app developer's dream come true. With Google's open source toolkit, you can easily build beautiful apps that work across platforms using a single codebase. This flexibility allows you to get your work out to the widest possible audience. Flutter is already being used by thousands of developers worldwide in a market where billions of apps are downloaded every year. Now is the right time to get ahead of the curve with this incredible tool. Flutter for Dummies is your friendly, ground-up route to creating multi-platform apps.From how to construct your initial frameworks to writing code in Dart, you'll find the essentials you need to ride the Flutter revolutionary wave to success. This book includes guidance on how to create an intuitive and stunning UI, add interactivity, and easily pull in data. You'll also see how Flutter features like Hot Reload—providing sub-second refreshes as you refine your work—help you make sure your app is a delight to use."--Publisher's website.